Kill the major the true story of the allied guerrilla hunt for the last Japanese forces in Borneo - Malone, Paul (Strategic Information and Research Development Centre, 2020)
Kill the Major is the true story of the allied guerrilla hunt for the last Japanese forces in Borneo during World War II.